Mechanochemical Synthesis of Visible Light Sensitive Titanium Dioxide Photocatalyst - Jan Šubrt; Jose M. Criado; Lórant Szatmáry; Maria J. Diánez-Millán; Nataliya Murafa; Luis A. Pérez-Maqueda; Vlasta Brezová (International Journal of Photoenergy)
Phase transition of anatase nanoparticles into the phases TiO2-II and rutile under grinding was studied. The addition of ammonium carbamate to the reaction mixture inhibits the phase conversion and the cold welding of particles. The UV-visible absorption spectrum showed narrowing the band gap width after grinding with an ammonium carbamate additive resulting in shift of the light absorption of the ground sample towards the visible region. By EPR, intensive formation of OH• radical at irradiation of the sample with both UV (λ > 300 nm) and visible (λ > 435 nm) light was observed. High photocatalytic activity of the ground sample in visible light region was demonstrated also by measurement of kinetics of the photocatalytic decomposition of 4-chlorophenol.